Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.jcta.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

h-Vectors of Gorenstein polytopes

Abstract: We show that the Ehrhart h-vector of an integer Gorenstein polytope with a regular unimodular triangulation satisfies McMullen's g-theorem; in particular, it is unimodal. This result generalizes a recent theorem of Athanasiadis (conjectured by Stanley) for compressed polytopes. It is derived from a more general theorem on Gorenstein affine normal monoids M: one can factor K[M] (K a field) by a "long" regular sequence in such a way that the quotient is still a normal affine monoid algebra. This technique reduce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 10 publications
2
85
0
1
Order By: Relevance
“…Stanley [18] noted that, in the case that an n-dimensional polytope P is r-Gorenstein, one has h * i (P) = h * n+1−r−i (P) for all r. Bruns-Römer [2] showed that if an r-Gorenstein polytope has a regular and unimodular triangulation, then the h * -vector is unimodal. For Lipschitz polytopes, such a triangulation is vouched for by Theorem 3.1 and with Proposition 4.2, we get the following.…”
Section: Ranked Posetsmentioning
confidence: 99%
“…Stanley [18] noted that, in the case that an n-dimensional polytope P is r-Gorenstein, one has h * i (P) = h * n+1−r−i (P) for all r. Bruns-Römer [2] showed that if an r-Gorenstein polytope has a regular and unimodular triangulation, then the h * -vector is unimodal. For Lipschitz polytopes, such a triangulation is vouched for by Theorem 3.1 and with Proposition 4.2, we get the following.…”
Section: Ranked Posetsmentioning
confidence: 99%
“…In [3], it is shown that a Gorenstein integer polytope with a regular unimodular triangulation has a unimodal δ -vector. In [2], it is shown that ∆ stab(r) n, k has a regular unimodular triangulation.…”
Section: Gorenstein R-stable Hypersimplicesmentioning
confidence: 99%
“…The G-property is related to the notion of Gorenstein polytopes [8], Gorenstein simplicial complexes, and Gorenstein rings [7,28] We call a sum w 1 + w 2 of two weight functions of a point configuration A coherent if…”
Section: Remark 22mentioning
confidence: 99%